Sistem Informasi Pendaftaran Calon Jama’ah Haji Pada Kantor Kementrian Agama Labuhan Batu Utara - Masitoh Ritonga; Inny Rahayu Rambe; Fasdiansyah Putra; Syaiful Zuhri Harahap (Journal of Student Development Information System (JoSDIS), 2021)
In this era of globalization computer is needed in all aspects of life is no exception in Hajj registration.. The same with the development of Information Systems.Whether or not an information depends on the information obtained. If an information produced is incomplete or incorrect, it can be said that decision making will be inappropriate and wrong target. The Office of the Ministry of Religious Affairs as the Ministry of Hajj still has many weaknesses. In addition to requiring a long time in registration, accuracy is also less acceptable.. With the support of information technology that exists today, data processing carried out today can be replaced with a web-based system . The data collection method used is observation, interview, and literature study. The programming used is website programming by using notped++ as an editor with PHP program language and MYSQL as data storage media. This study resulted in the Registration Information System of Hajj pilgrims candidates at the North Labuhan Batu Ministry of religious affairs office. Hopefully with this information system can improve the work process in handling the registration of prospective pilgrims.